Response of the coccolithophore Emiliania huxleyi to increased CO2 and Fe availability within the plankton food web - Lorenzo, M. Rosario (UMA Editorial, 2016)
Ocean acidification due to increased CO2 emissions derived from anthropogenic activities is affecting marine ecosystems at an unprecedented rate (IPCC 2013). Ocean acidification has the potential to affect the physiological processes due to increasing CO2 levels and lower pH (Riebesell & Tortell 2011). Ocean acidification also impacts trace metal solubility and speciation. Among all trace metals, Fe is the most essential for biological functions of phytoplankton. Coccolithophores is one of the taxa most affected by increased CO2 and the most important coccolithophore is Emiliania huxleyi. This species is responsible for a large fraction of the ocean calcium carbonate production and export to the deep ocean contributing to the regulation of the exchange of CO2 across the ocean-atmosphere interface (Rost & Riebesell 2004). Emiliania huxleyi has been widely studied in many different works, with one or more global change stressors either in laboratory or in natural conditions. However, there is a lack of knowledge on the response to interactive effects of ocean acidification and dissolved Fe at different levels in this species. The aim of this thesis is to gain deeper insight in the physiological response of E. huxleyi to increased CO2 and Fe availability within the food web using mesocosms and also under controlled laboratory experiments. For this purpose, two types of experiments were performed: a mesocosm experiment and a laboratory experiment. The mesocosm experiment and manipulated to achieve combinations of ambient and increased pCO2 and dFe to investigate the physiology response of the coccolithophorid Emiliania huxleyi within a natural plankton community. The experimental work was performed to elucidate the interactive effect of the exposure to UV radiation (UVR) with increased CO2 and/or different Fe levels. Mesocosm experiments showed a higher degree of realism compared to controlled laboratory experiments due to the semi-control conditions. The most important result was that Fe played the major role controlling the physiological response of Emiliania huxleyi in both systems. Fe also allow coping better the stress condition, increased CO2 and exposure to UV radiation, in mesocosm and laboratory experiment, respectively. The effects of increased CO2 were differential depending on the conditions of the experiment. In the mesocosm system, the effect of increased CO2 was detrimental in the majority of the physiological processes. But the effect of increased CO2 was differential under controlled cultures depending on each physiological process. This study demonstrates that Fe concentrations may control phytoplankton community structure in coastal ecosystems. Thus, in areas with high total Fe concentrations (particulate and dissolved Fe), the detrimental effects of increased pCO2 on these strains can be partially mitigated by enhanced dFe, possibly inducing cascading effects on food web dynamics, carbon export, and the rain ratio, finally affecting the exchange of CO2 across the oceanatmosphere interface. References: IPCC, 2013. Climate Change 2013: The Physical Science Basis. Contribution of Working Group I to the Fifth Assessment Report of the Intergovern- mental Panel on Climate Change. Riebesell U, Tortell PD (2011) Effects of ocean acidification on pelagic organisms and ecosystems. In: Ocean Acidification. Rost B, Riebesell U (2004) Coccolithophores and the biological pump: responses to environmental changes. In: Coccolithophores: from molecular process to global impact.
Keywords: Efecto invernadero - Aspectos del medio ambiente - Tesis doctorales; Ocean acidification; Fe availability; phytoplankton; physiology